The role of Pakistan Medical & Dental Council in steering undergraduate medical curriculum reforms in Pakistan - Gohar Wajid; Lubna Baig; Syeda Kauser Ali; Usman Mahboob; Ahsan Sethi; Rehan Ahmed Khan (Khyber Medical University Journal)
There has been an exponential increase in the number of medical colleges in Pakistan over the past few decades, especially in the private sector. Pakistan has a strong medical education system with 48 public sector and 75 private sector medical colleges. Around 16,625 new doctors graduate from these colleges annually, with more colleges currently in development.1 Pakistan Medical & Dental Council (PM&DC), being the major regulatory body in the country needs to ensure that the colleges produce high-quality, fit-for-purpose and safe physicians that are competent to meet the health needs of the population. Shaping the vision for 21st century medical education and steering undergraduate medical curriculum reforms is a major challenge for the regulatory body. Moreover, medical universities and medical colleges in the country are equally important stakeholders in pursuing these reforms. This editorial briefly reviews the medical curriculum guidelines recently released by the PM&DC and suggests how the curriculum can be reformed.